Hadith "Torture of Corpse because of Family Weeping": Problem and Solution | حديث تعذيب الميت ببكاء أهله: إشكالية وحلول - Ahmad Dahlan Ali Ahmadi (Al-Zahra : Journal for Islamic and Arabic Studies, 2010)
The research aims to clarify the intended meaning of one of prophetic traditions(hadith) that became a subject of controversy since the age of the companions(Sahabah). This hadith said that a person could be tortured by Allah in hisgrave, because his family’s cry for his death. The research reviews the differentviews of scholars (ulama) in the interpretation of the hadith, through the viewsof the companions, the old scholars, and the latecomers and the contemporaryscholars, by reference to annotation books of hadith and others. The researchfinds that scholars may have differed in dealing with the hadith to the fourmain opinions: some refused the hadith claiming that the narrator has beenmade a mistake in the process of telling the hadith, and some said that thehadith had been canceled (mansukh), and some understood the hadith as itstextual meaning, while some of them interpreted the hadith with differentinterpretations up to nine views. In the end of the research, the researcher haschosen the views of al-Imam al-Bukhari because of its strength evidences. Themethod of this research is critical method upon sanad (narrator) and matan(substance) of some hadis related to the topic. The writer refers to both theclassical and contemporary books.